A preliminary investigation on water birds and their relation with flood-control drain water quality in oil palm smallholdings - Sulai, Petra; Md Sharif, Badrul Azhar; Abu Bakar, Siti Nurhidayu; Abd. Rahman, Mohd Afendy; Shamsuddin, Siti Aisah; Hussin, Mohamed Zakaria (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Human modified landscapes such as oil palm planted areas can sustain water bird communities. This study aimed at quantifying the diversity of water birds at aquatic habitats in oil palm smallholdings in Tanjung Karang, Selangor. Seven water quality characteristics were measured, namely, pH, dissolved oxygen (DO), total dissolved substance (TDS), water temperature, salinity, conductivity and turbidity. Ground vegetation cover, stream width, water level and stream velocity were also measured. Twenty five line transects were established within the peat swamp forest-converted (PF) and mangrove forest–converted (MF) oil palm smallholdings. Between March and April 2013, a total of 315 water birds (seven species - six residents and one migratory species) were recorded. The species diversity of water birds was higher in MF than PF. At PF, species richness increased with water level and TDS, but decreased with salinity. At MF, species richness decreased with water level and turbidity. Flood-control drains and water quality are important for water bird conservation in oil palm planted areas.